A CHAPTER REVIEW: SELECTING LANGUAGE FOR MATERIALS WRITING: (The Routledge Handbook of Materials Development for Language Teaching-Routledge) - Zulkifli Surahmat; Ahmed Sardi; Muh. Firmansyah JN (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2023)
This chapter review will discuss the current topic in chapter 6 from a book entitled “The Routledge Handbook of Materials Development for Language Teaching-Routledge” Edited by Julie Norton and Heather Buchanan. The selection of grammar and the selection of vocabulary for the creation of English Language Teaching (ELT) course books have been the two main topics of this chapter. Given the homogeneity of many published materials, it is simple to believe that the subject of